2021
DOI: 10.5194/aab-64-315-2021
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism analysis and expression patterns of the <i>IGF1</i> gene in the Shitou goose

Abstract: Abstract. Insulin-like growth factor 1 (IGF1) is one of the endocrine hormones that plays an important role in regulating growth and development of animals. In this study, polymorphism in the 5′UTR and 3′UTR coding region and of the IGF1 gene was detected by DNA sequencing technology, and the abundance of IGF1 mRNA in various tissues at three growth stages of the Shitou goose was determined by quantitative real-time polymerase chain reaction (qRT-PCR). Moreover, the differential expression of IGF1 in various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Shitou geese are suitable for the study of goose muscle growth and development due to the advantages of fast growth and high meat production. A total of 290 differentially expressed genes (DEGs) were identified between large-size Shitou goose and small-size Wuzong goose by using RNA-seq [ 7 ]. An interaction network analysis showed that the genes related to protein synthesis were upregulated in expression in the Shitou goose compared to the Wuzong goose [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shitou geese are suitable for the study of goose muscle growth and development due to the advantages of fast growth and high meat production. A total of 290 differentially expressed genes (DEGs) were identified between large-size Shitou goose and small-size Wuzong goose by using RNA-seq [ 7 ]. An interaction network analysis showed that the genes related to protein synthesis were upregulated in expression in the Shitou goose compared to the Wuzong goose [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 290 differentially expressed genes (DEGs) were identified between large-size Shitou goose and small-size Wuzong goose by using RNA-seq [ 7 ]. An interaction network analysis showed that the genes related to protein synthesis were upregulated in expression in the Shitou goose compared to the Wuzong goose [ 7 ]. Histological analysis revealed that the Shitou goose had higher myofiber density and larger myofiber diameter at embryonic stages than the Wuzong goose [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al found that IGF-1 c.-366 A > C is associated with fat deposition in chickens and that this SNP affects IGF-1 expression through differences in transcription factor binding [ 75 ]. Tang et al found different levels of IGF-1 expression in goose breeds of different sizes, with significantly higher levels in large geese compared with that in small geese [ 76 ]. In summary, we suggest that introgression of Chinese domestic geese into Yili geese affects IGF-1 expression levels by increasing transcription factor Sp1 binding sites, which influence the body size of Yili geese.…”
Section: Discussionmentioning
confidence: 99%
“…The IGF1 and PAX7 genes are star genes and play an important role in regulating the growth and development of animals. In the goose, the IGF1 and PAX7 genes were both reported to be associated with muscle development (Tang et al., 2021; Wang et al., 2017). Thus, the above 29 genes may be candidate genes related to the muscle difference between the XHF geese and Zi geese.…”
Section: Figurementioning
confidence: 99%